Effects of Bisphenol A and Learning on the Distribution of GABAAα1 Receptors in the Rat Hippocampus and Prefrontal Cortex - Taherianfard, M.; Taci, A.A. (Нейрофизиология, 2015)
Bisphenol-A (BPA) is a widely distributed chemical having mixed estrogen agonist/antagonist properties. We investigated the effects of introduction of BPA and passive avoidance learning on the distribution of GABAAα1 receptors in the rat prefrontal cortex and hippocampus. BPA (5 and 50 mg/kg·day) was introduced by oral intake for 15 days; learning and memory were tested in a shuttle-box. The distributions of GABAAα1 receptors were investigated by an immunohistochemical procedure. The BPA treatment significantly decreased the density of GABAAα1 receptors in the prefrontal cortex and hippocampus. The distribution of these receptors was significantly denser in BPA-exposed rats subjected to learning than that in rats without learning. Thus, BPA treatment leads to down-regulation of GABAAα1 receptors in the prefrontal cortex and hippocampus. Learning a passive avoidance reaction provides upregulation of such receptors in these brain structures.